Expanding of Excimer Laser Photoablation’s Functionality in Ophthalmology - V. A. Alekseev; V. G. Kostin; A. V. Usoltseva; V. P. Usoltsev; S. I. Yuran (Приборы и методы измерений, 2021)
One of the significant weaknesses of excimer laser-based vision correction devices is the difficulty of achieving a required change in the refractive properties of the cornea to sharply focus the image on the retina with distance from the working area (ablation zone) center to the periphery due to a change in the laser beam incidence angle. The study is aimed at improving the quality of laser action on the eye cornea by introducing an optical corrective system into the existing excimer laser vision correction equipment, ensuring the coincidence of the direction of the laser beam incidence on the corneal surface with the normal.It has been shown that the greater the reflection coefficient, the lower the absorbed energy, and the shallower the laser radiation penetration and ablation depths, which reduces the laser action opportunities and quality. When using excimer laser vision correction devices, it has been proposed to change the angle of the laser beam incidence on the cornea with a distance from the working area (ablation zone) center to the periphery during the surgery by introducing an optical corrective system based on a lightweight controllable and movable mirror, which allows achieving the coincidence of the direction of the laser beam incidence on the corneal surface with the normal.The studies have shown that the coincidence of the laser beam incidence on the corneal surface at any point with the normal when using a priori data on the specifics of the patient's eye allows expanding the functional opportunities of excimer laser photoablation, i. e., expand the ablation zone by 30 % and eliminate the possibility of errors caused by the human factor. The technique proposed can be used for excimer laser vision correction according to PRK, LASIK, Femto-LASIK, and other methods. To implement this approach, a patented excimer laser vision correction unit has been proposed with a PCcontrolled optical shaping system comprising galvo motor platforms and galvo mirrors installed on them.